Rattus argentiventer - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Rattus argentiventer (Robinson and Kloss, 1916). J. Str. Br. Roy. Asiat. Soc., 73: 274. TYPE LOCALITY: Indonesia, "west coast of" Sumatra, Pasir Ganting. DISTRIBUTION: Thailand and Indochina to Java, Borneo; Mindoro and Mindanao (Philippines); introduced on Lesser Sunda Isis., Sulawesi, and New Guinea. COMMENT: Includes pesticulus; see Musser, 1973, Am. Mus. Novit., 2511:1-30. Reviewed by Musser, 1981, Bull. Am. Mus. Nat. Hist., 169(2):67- 176. ISIS NUMBER: 5301410011058010001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 5), pp. 504-560 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 547, DOI: 10.5281/zenodo.7353037